Bright and Robust Phosphorescence Achieved by Non‐Covalent Clipping. (3rd March 2021) - Li, Zijian; Han, Yifei; Nie, Fude; Liu, Mingyang; Zhong, Hua; Wang, Feng
Abstract: Phosphorescent materials with bright emission in versatile media are important for their practical applications, which require to lower the susceptibility of triplet excitons to surroundings. Herein a non‐covalent clipping strategy has been developed to attain this objective, by designing a tweezer receptor to encapsulate Pt II ‐based triplet emitters through two‐fold π‐stacking interactions. The Pt II emitters display robust phosphorescence by virtue of synergistic rigidifying and shielding effects, which are hardly influenced by emitter concentration, oxygen content, and solvent polarity changes. The phosphorescent colors are elaborately modulated by varying ligand substitutes on Pt II emitters. Circularly polarized phosphorescence is further amplified for chiral Pt II emitters, by taking advantage of dual phosphorescence and chirality enhancement upon non‐covalent tweezer complexation. Overall, the clipping approach paves the way for the development of high‐performance phosphorescent materials with bright emission, environmental robustness, and facile color tunability. Abstract : A pre‐organized tweezer receptor has been constructed to encapsulate triplet emitters. The emitters displayed bright and robust phosphorescence in versatile media upon non‐covalent clipping, regardless of emitter concentration, oxygen content, and environmental polarity variations.